Umakhweyane: A Musical bow and its contribution to Zulu music - Dargie, David (International Library of African Music, 2007)
Nearly all musical bows used in the indigenous music of southern Africa are single string melody instruments. The player uses the overtones of the string to produce melody. This is done in various ways according to how the bows are constructed, what sort of resonator is used, and how the bow is played. Some bows have an attached resonator, with others the player uses her/his mouth as resonator. Bows may be played by percussion (striking the string), by plucking, and by friction (rubbing the string or the bow stick).
Keywords: African Music